Guest Editorial: EDUCATIONAL RESTRUCTURING IN QUÉBEC: THE THIRD WAVE OF REFORM - Smith, William J.; Foster, William F. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1999)
This special issue of the McGill Journal of Education is devoted to the current reform of education in Québec. All of the authors represented in this publication are both observers of and participants in the Québec education scene. They come from the Ministry, the university, school boards and schools, and together provide an eclectic perspective on the reform.